2023
DOI: 10.3389/fimmu.2023.1170569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neoadjuvant immunotherapy and traditional neoadjuvant therapy for resectable esophageal cancer: a systematic review and single-arm and network meta-analysis

Abstract: ObjectiveThis systematic review and meta-analysis aimed to investigate the role of neoadjuvant immunochemotherapy with or without radiotherapy [NIC(R)T] compared to traditional neoadjuvant therapies, without immunotherapy [NC(R)T].Summary background dataNCRT followed by surgical resection is recommended for patients with early-stage esophageal cancer. However, it is uncertain whether adding immunotherapy to preoperative neoadjuvant therapy would improve patient outcomes when radical surgery is performed follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…8 17 Another systematic review and network meta-analysis demonstrated that there were no significant differences between NICRT and NCRT with regard to pCR or mPR rates, and both were superior to NICT. 24 Further randomized controlled studies are required to validate whether the tricombination neoadjuvant therapy approach yields a superior pathological response compared with standard nCRT. The ultimate objective of improving pCR is to provide survival benefits to patients.…”
Section: Open Accessmentioning
confidence: 99%
“…8 17 Another systematic review and network meta-analysis demonstrated that there were no significant differences between NICRT and NCRT with regard to pCR or mPR rates, and both were superior to NICT. 24 Further randomized controlled studies are required to validate whether the tricombination neoadjuvant therapy approach yields a superior pathological response compared with standard nCRT. The ultimate objective of improving pCR is to provide survival benefits to patients.…”
Section: Open Accessmentioning
confidence: 99%
“…[ 3 ] Although most patients with early and intermediate-stage esophageal cancer receive the systemic surgical and neoadjuvant/adjuvant therapies, a considerable proportion of esophageal cancer patients will still experience the recurrence and metastasis after the surgery, even among patients without lymph node metastasis. [ 4 , 5 ] Therefore, the causes and mechanisms of postoperative recurrence and metastasis in esophageal carcinoma patients need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%